Qu'en est-il du roman graphique portugais? Enjeux linguistiques et culturels - Duarte, Isabel Margarida (2018)
The graphic novel, with a strong syncretism with respect to genre, has become nowadays a form of textuality resulting from more or less complex relationships between iconic signs and verbal signs, with iteratively revisited questions about its belonging especially to literature, considering, on the one hand, the role played by a non-verbal language and, on the other hand, its presumed inscription in mass culture, as regards its reception. It is within this framework summarily traced that we consider two axes of reflection: what about a presence of Portuguese graphic novels? What linguistic and cultural issues can be exploited in FL class? The corpus is composed of two graphic novels, Arte suprema and Rei by A. J. Gonçalves and R. Zink.